Clinical and biological evaluation of one-step procedure covering of exposed surfaces of root with connective tissue free graft by envelope method and applying Citric Acid - A. Miremadi (Tehran University of Medical Sciences, 1996)
In present study, 12 patents (10 F/2M) of 19-42 years with gingival recession in 14 sites of the mouth were recruited. Inclusion criteria were considered and following primary treatments, measurements (sulcus depth as well as depth and width of gingival recession and distance between a fixed point and gingival margin ) were done. Free gingival graft from palate was harvested by envelope technique and using saturated citric acid. The distance between a fixed point and gingival margin   and sulcus depth were recorded after 1,2,3,6 month post surgery. In addition, The depth of gingival recession from CEJ was measured 6 month post operatively. Based on tables and statistical methods, the root coverage was 65.35%. by 3 weeks after surgery, the graft was united with the adjacent tissues.